Role of Civil Servants in Synchronization of Regional Legislation with the Regional Medium -Term Development Plan (RPJMD) - Suyetno Suyetno; Hendry Rumengan; Nathanael Tarunadjaya (Publik : (Jurnal Ilmu Administrasi), 2025)
Synchronization between local legislative products and the Regional Medium-Term Development Plan (RPJMD) is a crucial element to ensure an effective development direction. However, disharmony often arises between regulations issued by the Regional People's Representative Council (DPRD) and policies in the RPJMD. This study aims to analyze the role of the State Civil Apparatus (ASN) within the DPRD Secretariat in the synchronization process of local legislation with the RPJMD, identify the obstacles encountered, and formulate strategies to strengthen its role. This research employs a descriptive qualitative approach with a case study in Manado City. Data collection techniques include in-depth interviews, documentation studies, and Focus Group Discussions (FGDs) with ASN, DPRD members, and regional planners. The results are expected to provide an in-depth analysis and strategic recommendations that can strengthen the synergy between the legislative and development planning processes, thereby supporting the enhancement of local governance. Thus, this study concludes that the role of civil servants at the Manado City Council Secretariat in synchronizing regional legislation with the RPJMD is crucial, but still limited to administrative aspects. To strengthen synchronization, efforts are needed to continuously improve the capacity of civil servants, build a motivation-based work culture, strengthen inter-agency coordination, and utilize digital technology in regional legislative governance.